DIETARY HABITS AS INDEPENDENT PREDICTORS OF ANEMIA AMONG FEMALE ADOLESCENT STUDENTS AT SENIOR HIGH SCHOOL 1 AJIBARANG - Difa Ifa Khairunnisa; Hafiidhaturrahmah Hafiidhaturrahmah; Tri Lestari; Qodri Santosa (Fakultas Kedokteran Universitas Jenderal Soedirman, 2026)
Anemia remains a major public health problem, affecting approximately 29.9% of adolescents globally. Dietary habits are a major modifiable risk factor; however, their role as an independent predictor in rural Southeast Asian settings is not yet fully documented. This study aimed to identify dietary habits and evaluate them as an independent predictor of anemia among female adolescents at Senior High School 1 Ajibarang, Central Java, Indonesia. A cross-sectional study was conducted involving 261 participants (aged 14–17 years) recruited through total sampling. Dietary habits were assessed using a semi-quantitative Food Frequency Questionnaire (FFQ), while anemia status was determined by hemoglobin levels measured via a Point of Care Testing (POCT) device. The prevalence of anemia was 41.0%, with 58.2% of respondents exhibiting poor dietary habits. Bivariate analysis showed a significant association between dietary habits and anemia (p = 0.027; OR = 1.777; 95% CI: 1.067–2.962). The multivariate logistic regression analysis, adjusted for age and socioeconomic confounders, revealed that dietary habits emerged as the sole independent predictor of anemia (p = 0.024). Respondents with poor dietary habits were 1.79 times more likely to be anemic compared to those with good habits (AOR = 1.793; 95% CI: 1.075–2.991). In conclusion, dietary habits are the primary independent predictor of anemia among female adolescents in this rural Indonesian setting.